A influ??ncia da qualidade percebida, do valor percebido e do custo de mudan??a sobre a lealdade dos usu??rios do servi??o de sa??de suplementar - Neri, Anna Sofia Costa (2015)
The service sector has shown steady expansion in the Brazilian economy, reflecting directly expressive financial results for the country. The health insurance sector is inserted in this context and in the face of disability in the provision of public health services to the population in a universal way, it presents itself as an indispensable element in the framework currently in force in Brazil. The sector's growth has provided an intense competition between operators of health plans by requiring these companies seek to capture and keep customers loyal to their services, thus remaining competitive. However, a considerable amount of customer complaints of this market is presented by the National Health Agency. Identifying the relationship between perceived quality, perceived value and cost of change as trainers concepts of customer loyalty, this study sought to understand that relationship with users of supplemental health services. These, in turn, provided information by completing a validated questionnaire that was used to build a theoretical model analyzed by structural equation modeling with the use of partial least squares technique (PLS). The theoretical framework used in this paper presents the trainers concepts and customer loyalty influencers. The results demonstrated an understanding of users and service aspects of the study, both in its relationship to the health insurance, as in its relationship with the hospital use most with your plan. Relations between the concepts presented in the model were mostly positive, except for the influence of the value perceived by the customer in relation to the health plan on loyalty to the hospital, and the influence of the value perceived by the customer in the hospital on customer loyalty to the health plan.